Recent Update on PET/CT Radiotracers for Imaging Cerebral Glioma - Kim, Dongwoo; Lee, Suk-Hyun; Hwang, Hee Sung; Kim, Sun Jung; Yun, Mijin (Nuclear medicine and molecular imaging, 2024)
Positron emission tomography/computed tomography (PET/CT) has dramatically altered the landscape of noninvasive glioma evaluation, offering complementary insights to those gained through magnetic resonance imaging (MRI). PET/CT scans enable a multifaceted analysis of glioma biology, supporting clinical applications from grading and differential diagnosis to mapping the full extent of tumors and planning subsequent treatments and evaluations. With a broad array of specialized radiotracers, researchers and clinicians can now probe various biological characteristics of gliomas, such as glucose utilization, cellular proliferation, oxygen deficiency, amino acid trafficking, and reactive astrogliosis. This review aims to provide a recent update on the application of versatile PET/CT radiotracers in glioma research and clinical practice.